HOW SHOULD THE WELFARE OF FETAL AND NEUROLOGICALLY IMMATURE POSTNATAL ANIMALS BE PROTECTED? - Campbell, Madeleine L.H. (Anim Welf, 2014)
Legal protection of the welfare of prenatal animals has not previously been addressed as a discrete subject within the academic literature on animal welfare, ethics and law. This paper aims to rectify this by reviewing the protections (or absence of protections) provided for fetuses by existing legislation in various jurisdictions, and considering the extent to which legal protection of animal fetuses can be justified on animal welfare grounds. Questions related to the need to protect the welfare of neurologically immature postnatal animals are also considered. We argue that there are reasons to protect animal fetuses, both in order to protect fetuses themselves against possible suffering, and in order to protect the animals which fetuses will become against negative welfare impacts that originate prenatally. We review the science on whether fetuses can suffer, and argue that extant regulations do not fully reflect current scientific understanding. Following the precautionary principle, we further argue that regulators should consider the possibility that foetuses and neurologically immature postnatal animals may suffer due to subcortically based ‘raw basic affects’ (i.e. relatively undifferentiated experiences of discomfort suggested to be generated by neural processing at levels below the cerebral cortex). Furthermore we show that there are reasons for affording fetuses protection in order to safeguard the long-term welfare of future animals. However, it may be possible to provide such protection via rules or laws relating to the use of certain techniques and the management of pregnant animals, rather than via direct legal protection of fetuses themselves. In order to provide such protection effectively we need to know more about the relationship between maternal nutrition, stress, exercise, management and fetal health, and about the impact of the timing of a fetal insult on long-term postnatal welfare.